Soil borne fungi of cultivated lands of Biratnagar, Nepal - Koirala, Umesh (Nepalese Journal of Biosciences, 2013)
DOI: http://dx.doi.org/10.3126/njbs.v2i0.7503 Nepalese Journal of Biosciences 2 : 151-153 (2012)